Molecular Detection and Phylogenetic Analysis of Cucumber Mosaic Virus Infecting Bhut Jolokia (Capsicum chinense Jacq.) of Assam - Borah, Munmi; Kumar, R. Gowtham; Siddappa, Sundaresha (International Journal of Economic Plants, 2019)
Prevalence of Cucumber mosaic virus (CMV) in Bhut Jolokia (Capsicum chinense Jacq.) in Assam was confirmedby reverse transcription-polymerase chain reaction (RT-PCR). The symptomatic expression of CMV infection onto Bhut Jolokia was confirmed as chlorotic yellow mosaic appearance of the leaves, smaller leaves, reduction of plant growth, mosaic and mottling of infected leaves, leaves showing shoe-string or filliform symptom and leaf puckering based on RT-PCR. This is the first report on molecular characterization of CMV in Assam, India. The RT-PCR diagnosis revealed presence of CMV with a band length of 593bp which has been obtained from CMV infected samples. The amplified coat protein gene of CMV was cloned and sequenced. Phylogenetic analysis of coat Protein gene of CMV showed close relatedness with African isolates of sub group IB and other isolates of the world.